The Influence Of Human Resource Capacity And The Use Of Regional Property Information Technology On The Quality Of Financial Reports Through Regional Property Management - Fajar Hidayanto; Suryawati, Dina; Wulandari, Kusuma (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of human resource capacity and the use of information technology on the quality of financial reports with the management of Regional Assets as a mediating variable. The background of the study is based on the important role of competent human resources and optimal utilization of information technology in realizing accountable regional asset management, which ultimately has implications for the quality of regional government financial reports. The research method uses a quantitative approach with a survey technique with PLS-SEM (SmartPLS 3.0). The study population amounted to 114 apparatus related to the management of BMD and the preparation of LKPD. A sample of 89 respondents was determined using the Slovin formula (e = 5%) and stratified random sampling based on roles (asset administrators, eBMD operators/preparers of Regional Government Financial Reports, and managers of Regional Assets in Situbondo Regency).